2014
DOI: 10.1016/j.ygeno.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Decoding complex patterns of genomic rearrangement in hepatocellular carcinoma

Abstract: Elucidating the molecular basis of hepatocellular carcinoma (HCC) is crucial to developing targeted diagnostics and therapies for this deadly disease. The landscape of somatic genomic rearrangements (GRs), which can lead to oncogenic gene fusions, remains poorly characterized in HCC. We have predicted 4314 GRs including large-scale insertions, deletions, inversions and translocations based on the whole-genome sequencing data for 88 primary HCC tumor/non-tumor tissues. We identified chromothripsis in 5 HCC geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 54 publications
0
49
1
Order By: Relevance
“…HCC stratified by low ALB and APOB expression were associated by Gene Set Enrichment Analysis (GSEA) with increased cell cycle progression, ribosome biogenesis and nucleotide synthesis, and reduced oxidative phosphorylation (data not shown). Because ALB expression accounts for 20% of cellular mRNA (Uhlen et al, 2015) and APOB consumes large amounts of cellular energy by facilitating VLDL secretion (Egusa et al, 1985), there may be selection for ALB or APOB inactivating mutations to divert energy into cancer-relevant metabolic pathways (Fernandez-Banet et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…HCC stratified by low ALB and APOB expression were associated by Gene Set Enrichment Analysis (GSEA) with increased cell cycle progression, ribosome biogenesis and nucleotide synthesis, and reduced oxidative phosphorylation (data not shown). Because ALB expression accounts for 20% of cellular mRNA (Uhlen et al, 2015) and APOB consumes large amounts of cellular energy by facilitating VLDL secretion (Egusa et al, 1985), there may be selection for ALB or APOB inactivating mutations to divert energy into cancer-relevant metabolic pathways (Fernandez-Banet et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…If this were the case, however, the mutants carrying mutations induced by Ar or Fe ion beams would be unique resources for the study of de novo epiallele formation, since details of the genomic rearrangements in the mutant genomes could be elucidated by NGS. Moreover, a gene fusion event could possibly result from the genomic rearrangements, and it has been reported that the fusion genes often present an aberrant expression pattern (Fernandez-Banet et al, 2014). The Ar-and Fe-ion beams have the potential to induce epiallele formation and gene fusion and thus extend a spectrum of mutant phenotypes beyond those generated by other mutagens.…”
Section: Discussionmentioning
confidence: 99%
“…To date, we are aware of only one study that investigated the role of chromothripsis in the incidence of HCC. In this study, chromothripsis and CIN were found to recurrently affect chromosomal arms 1q and 8q to create gene amplifications, suggesting that chromothripsis might contribute to hepatocarcinogenesis[33]. It seems that more attention should be paid to this concept.…”
Section: Genomic Instabilitymentioning
confidence: 99%
“…Although the distribution of aberrant chromosomal arms differs among HCCs, numerous studies have shown, using aCGH data and SNP arrays, that certain regions are frequently affected in HCC, including gains in chromosomes 1q, 5p, 6p, 7q, 8q, 17q, and 20q and losses in 1p, 4q, 6q, 8p, 9p, 13q, 14q, 16p-q, 17p, 21p-q, and 22q[28-33]. These findings reflect a high degree of CIN in HCC[34], contributing to hepatocarcinogenesis.…”
Section: Genomic Instabilitymentioning
confidence: 99%